2015
DOI: 10.1111/jfb.12620
|View full text |Cite
|
Sign up to set email alerts
|

Opposite selection on behavioural types by active and passive fishing gears in a simulated guppy Poecilia reticulata fishery

Abstract: The present study assessed whether fishing gear was selective on behavioural traits, such as boldness and activity, and how this was related with a productivity trait, growth. Female guppies Poecilia reticulata were screened for their behaviour on the shy-bold axis and activity, then tested whether they were captured differently by passive and active fishing gear, here represented by a trap and a trawl. Both gears were selective on boldness; bold individuals were caught faster by the trap, but escaped more oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 56 publications
1
62
0
Order By: Relevance
“…The authors showed angling-induced selection is expected to consistently act on activity-related traits (e.g., swimming distance or exploration rate), while selection on home range should only be consistently strong when fishing is restricted to fixed position. Consistent with these expectations, in experimental studies high swimming activity has been found to consistently relate to capture probability in gill-nets and traps across a range of species [21,22,28], and in the wild Olsen et al [29], reported no fishing-induced selection operating on home range extension in Atlantic cod, Gadus morhua , fished with a variety of passive gear types in a Norwegian fjord. By contrast, in an angling context, Alós et al, [30] reported negative selection differentials acting on both home range extension and swimming activity in angler-exploited pearly razor fish, Xyrichthys novacula , in the wild, and the correlation between swimming activity and vulnerability to angling is overall variable and inconclusive (positive finding: [31]; negative: [29,3234] mixed evidence: [35,36]).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The authors showed angling-induced selection is expected to consistently act on activity-related traits (e.g., swimming distance or exploration rate), while selection on home range should only be consistently strong when fishing is restricted to fixed position. Consistent with these expectations, in experimental studies high swimming activity has been found to consistently relate to capture probability in gill-nets and traps across a range of species [21,22,28], and in the wild Olsen et al [29], reported no fishing-induced selection operating on home range extension in Atlantic cod, Gadus morhua , fished with a variety of passive gear types in a Norwegian fjord. By contrast, in an angling context, Alós et al, [30] reported negative selection differentials acting on both home range extension and swimming activity in angler-exploited pearly razor fish, Xyrichthys novacula , in the wild, and the correlation between swimming activity and vulnerability to angling is overall variable and inconclusive (positive finding: [31]; negative: [29,3234] mixed evidence: [35,36]).…”
Section: Introductionmentioning
confidence: 62%
“…The lack of relationships among activity and vulnerability that we documented disagreed with the study hypothesis, but is consistent with most previous empirical work on the behavioural determinants of angling vulnerability in a range of species [33,34], implying species-specific or gear-specific (natural vs. artificial bait) effects. Relative to activity, other personality traits not assessed in our study such as boldness [25,28] or aggression [38] likely play a larger role in angling vulnerability than bait encounters alone.…”
Section: Discussionmentioning
confidence: 99%
“…; Diaz Pauli et al. ). Therefore, increased timidity as an evolutionary response to size‐selective fishing will negatively affect catch rates (Philipp et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, differences in the propensity of wild animals to enter traps or take bait selects for certain behavioural types (e.g. Wilson et al, 1993;Garamszegi et al, 2009;Carter et al, 2012;Stuber et al, 2013;Diaz Pauli et al, 2015;Niemelä et al, 2015). This is probably also true of physiological and/or performance traits, although research on this question is lacking (but see Killen et al, 2015).…”
Section: To Control For Population Sampling Bias (Including Domesticamentioning
confidence: 99%